Towards an adapted MHP strategic capabilities model for moderating challenges to quality music festival management. Issue 2 (5th June 2017) - Simon, Alan; Parker, Alastair; Stockport, Gary; Sohal, Amrik
Abstract : Purpose: The music festival industry is challenged by intense competition and financial exigency. As a result, many festivals have either folded or are currently struggling. Therefore, the purpose of this paper is to show that motivator-hygiene-professional (MHP) strategic capabilities (SCs) are positively associated with quality music festival management thereby providing a playbook for potentially mitigating these challenges. Design/methodology/approach: The mixed methods research design comprised a case study of a leading event management company as well as nation-wide in-depth interviews and questionnaire survey. The authors initially confirmed the nature of the challenges to the industry from the case study and the in-depth interviews. The authors then developed an MHP Model of 15 SCs that were identified from the literature and the qualitative research. The relationship of the MHP SCs model to quality music festival management was tested in the questionnaire survey. Findings: The respondents suggested that all the SCs were related to quality music festival management. However, Professional SCs were considered comparatively less important than motivator and hygiene SCs. Across all three groups, interviewees highlighted the significance of artists, site and operational planning, financial and stakeholder management and ticket pricing. In addition, careful planning, delegation and quality focus, problem solving, resolve and flexibility, leadership and vision, communication and innovation were considered conducive to the quality management of music festival organisations. Practical implications: The MHP SCs model and dimensions of quality management offer music festival event managers a detailed practical playbook for moderating challenges to music festival management. In essence the authors provide the specific drivers that festival managers should best focus their attention upon. Visionary leadership, artist differentiation, innovation, customer service and flexible management have priority. Originality/value: The findings add to the festival management literature by demonstrating the importance of motivator, hygiene and additional professional SCs for moderating challenges to the music festival industry. To the best of authors' knowledge, no previous studies have directly investigated specific SCs critical for quality event and festival management. In particular, the academic significance of this paper is that the authors have combined Herzberg's motivator and hygiene factors with SCs, which are in essence success drivers, to create a novel holistic MHP SCs model for quality music festival management. Further explanatory insight is gained by the addition of a third factor of professional SCs.